Aspects of Early Upaniṣadic Exegesis - Andrijanić, Ivan (Array, 2011)
The article deals with techniques of upaniṣadic interpretation where two sets of rules are distinguished. In the article it is acclaimed that one set of six rules comes from pūrva-mīmāṃsā, but another may be genuine vedāntic.